THU0298 Long term outcome of patients with takayasu arteritis- a single centre study. (15th June 2017) - Goel, R; Danda, D; Joseph, G; Nair, A; Jayseelan, V; Jayaseelan, L; Kumar, S; Bacon, P
Abstract : Background: Takayasu Arteritis (TA), a large vessel vasculitis is characterised by a variable clinical course and outcome that differs across populations. Most studies are limited by small sample size. Objectives: (i) To study treatment outcome in our TA patients with a follow up of ≥12 months (ii) Construct a prediction model for subset of patients with sustained inactive disease. Methods: Consecutive patients with TA attending our clinics between 1998 and April 2016 were recruited. Details of baseline demography, clinical profile, angiography, disease extent using DEI.Tak, laboratory parameters and TADS (Takayasu arteritis damage score) were recorded. At each follow up visit, disease activity was assessed by Indian Takayasu Activity score (ITAS-2010 (CRP) and imaging, while damage was assessed by TADS for patients who followed up for ≥12 months (retrospectively for 179 and prospectively for 72 patients). Treatment response was classified as complete response (CR), partial response and no-response. Sustained inactive disease was defined as maintenance of CR throughout the follow up with steroid dose reduced to ≤5mg/day. Relapse was defined as return of active disease after CR. Statistical analysis was performed using SPSS-16. Intergroup comparisons were performed by nonparametric test. Logistic regression was used for determining independent associations. Optimal cut off values were determined using receiver operating curve and prediction model was constructed. Efficacy of medications was compared by Cox proportional hazards model. Results: Baseline details were noted for 503 patients: mean age at onset of 25.6±11.1 years, disease duration 12 (6–48) months, diagnostic delay 6 (3–24) months) and 77.9% were females. Among 251 patients with follow up of at least 12 months, 95.2% received steroids along with II line immunosuppressant in 93.6% (mycophenolate in 63.7%). Tocilizumab was given induction or rescue therapy to 44 patients. Revascularisation procedures were performed in 71.7%. Complete (ITAS 2010 = 0, CRP <6mg/L, angiowise non-progression) and partial response was achieved in 176 patients (70.1%) and 42 (16.7%) respectively within 6 months. During a median follow up of 42 (IQR: 24–81) months, 116 (46.2%) maintained complete response till their last follow up with cumulative relapse free survival of 83%, 70% and 55% at 1, 2 and 3 years respectively. A model including baseline CRP≤6.1mg/L, type 4 disease and DEI.Tak <9 predicted sustained inactive disease with an AUC of 70.2 (63.3–77.2, p=0.000). Initial steroid dosage of 0.5mg/kgday was similar to 1mg/kg/day in terms of response or relapse. Overall, there were only 15 (5.9%) patients who never responded to treatment. There were 2 fatalities. At the last visit, 176 (70.5%) had stable disease. Damage progression (delta TADS) was lower in patients with sustained inactive disease than the rest, p=0.000. Conclusions: Medical management arrested disease activity, damage progression and mortality in our cohort. Low baseline CRP and DEI.Tak scores and type 4 disease independently predicted sustained inactive disease. Disclosure of Interest: None declared